Prevalence of risky sexual behavior and associated factors among Injibara University students, Northwest Ethiopia - Adal, Mekdes Abera; Abiy, Saron Abeje; Reta, Mebratu Mitiku; Asres, Mezgebu Silamsaw; Animut, Yaregal (Frontiers in Reproductive Health, 2024)
Introduction Engaging in risky sexual behaviors can lead to HIV infection, sexually transmitted infections, and unintended pregnancy among youths. University students had greater sexual risks for many reasons. Therefore, this study aimed to assess the magnitude and associated factors of risky sexual behaviors among regular undergraduate students at Injibara University, Northwest Ethiopia. Methods A cross-sectional study was conducted at Injibara University from 20 January to 30 2020. Multistage sampling was employed to select 770 students. Data were collected using a semistructured self-administered questionnaire. A binary logistic regression model was used to identify factors associated with risky sexual behavior. Adjusted odds ratios with 95% CIs were determined, and variables with P-values <0.05 were considered significant. Result A total of 770 students participated in the study, providing a response rate of 100%. In this study, 294 (38%, 95% CI: 35%, 42%) students engaged in risky sexual behaviors. Risky sexual behavior was significantly associated with not tested for HIV (AOR = 1.62, 95% CI: 1.15–2.31), peer pressure (AOR = 1.90, CI: 1.37–2.64), basic HIV knowledge (AOR = 2.16, CI: 1.65–2.89), substance use (AOR = 3.56, CI: 2.11–6.06), watching pornography videos (AOR = 1.58, CI: 1.11–2.23), and HIV risk perception (AOR = 1.37, CI: 1.02–1.91). Conclusion and recommendation A substantial proportion of university students in this study engaged in unsafe sexual behavior. Risky sexual behaviors are more likely to occur when students are under peer pressure, use substances, have no perceived HIV risk, watch pornography, and have inadequate basic HIV knowledge. Therefore, tailored strategic interventions such as life skill training should be designed to bring about positive behavioral changes among university students.